Documentation and analysis of some Picasso's paintings by using hyperspectral imaging technique to support their conservation and stylistic matters. Issue 1 (November 2020) - Picollo, Marcello; Casini, Andrea; Cucci, Costanza; Stefani, Lorenzo; Jiménez-Garnica, Reyes; Fuster-López, Laura
Abstract: Imaging Spectroscopic techniques, also known as hyperspectral imaging, have been utilized in museums and conservation laboratories for documentation purposes and in support of restoration treatments on different types of artworks and archaeological objects. For more than a decade, several studies and research projects have been devoted to customize imaging spectroscopic instrumentation and methodologies to the specific needs of art conservation and applications in the museum context. Other issues arise such as the need to develop new image processing software, including the mosaicking of image-cubes, new pigment identification and mapping methods, visualization, and archiving of the results. The present communication reports the data obtained on two canvas paintings made by Picasso in 1917, presently in the permanent collection of the Museu Picasso in Barcelona. The hyperspectral data have been used to document his artistic technique and to define the chemical composition of the palette. In addition, these data supported the surface observations of the morphology and crack patterns of the paint layers in order to get a better understanding of the damage found. This study was carried out in the framework of an inter-institutional research project aimed to gain an insight into the failure mechanisms of modern and contemporary paintings.